KNOWLEDGE OF IMPROVED LIVESTOCK AND POULTRY FARMING PRACTICES AMONG TRIBAL WOMEN OF WESTERN GHAT REGION OF NEDUMANGADU TALUK IN THIRUVANANTHAPURAM DISTRICT - R.S.Jiji and R.Vijayan (J. Vet. Anim. Sci., 2012)
This is a study on the knowledge of improved cattle, goat and poultry farming practices among the tribal women of western ghat region of Nedumangadu taluk in Thiruvananthapuram district, Kerala. Members of four Self help groups operating under Kudumbasree in the Cheruppani tribal settlement area were studied. An arbitrary knowledge test was used to measure the respondents’ knowledge of cattle, goat and poultry farming. Data were collected through both questionnaire and interview methods. Half of the respondents (50%) had medium knowledge of cattle farming. More number of respondents fell in the low knowledge category (32.14%) than the high (17.86%). Majority of the respondents (69.64%) had medium knowledge of goat farming. The number of respondents in the high knowledge category (21.43%) was more than that of low (8.93%). As for knowledge of poultry farming, almost equal number of respondents belonged to the medium (39.29%) and low (41.07%) categories. Only a few had high level of knowledge (19.64%) in poultry farming. Respondents’ knowledge of scientific goat farming ranked first (0.63) followed by that of cattle farming (0.53) and poultry farming (0.48).